Assessment of Psychological Well-being among Enforcement Officers during the Movement Control Order (MCO) in Malaysia - Jong Jee Leong; Muhammad Idris Bullare @ Bahari; Mohd. Dahlan Abdul Malek (2020)
Malaysia has enforced Movement Control Order (MCO) starting on 18 March 2020 in order to fight the global COVID-19 virus. The pandemic has put the law enforcers in a great challenge to protect the interest and rights of consumers. This study is aimed to examine the impact of work conditions during MCO on psychological well-being of enforcement officers. In addition, it is also crucial to discover the level of psychological well-being among the enforcement officers during the MCO. Besides, this study also aims to find out the level of psychological well-being among the enforcement officers based on their respective working conditions during the MCO. A total of 441 enforcement officers have participated in this study after cluster sampling was conducted. The Malay Ryff’s Psychological Well-Being Scale (PWBS) (Short Version) was used to identify the level of psychological well-being as well as to test the hypotheses of the study. Data was accumulated by using google form and the dataset was analysed by using IBM SPSS Statistic version 25 and SmartPLS Professional version 3.2.8. The result and limitations were discussed in this study.